PENAMBAHAN TEPUNG RUMPUT LAUT EUCHEUMAA COTTONII HASIL FERMENTASI BIOFLOKULAN PADA PAKAN KOMERSIL IKAN NILA (Oreochormis niloticus) - Wulan Rahmania; Salnida Yuniarti Lumbessy; Dewi Putri Lestari (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2023)
This research aims to analyze the addition of Eucheuma cottonii sea weed flour from fermented bioflocculants on commercial food of tilapia (O. niloticus) feed. This research was conducted for 50 days at the Productionand Reproduction Laboratory of the Aquaculture Study Program, Department of Fisheries and Marine Sciences, Faculty of Agriculture, University of Mataram. This research used an experimental method with a completely randomized design (CRD) consisting of 4 treatment level sand 3 replications namely: P1 (commercial feed), P2 (90% commercial feed + 10% seaweed flour), P3 (80% commercial feed + 20% seaweed flour), P4 (70% commercial feed) + seaweed flour 30%). Parameters measured are the growth of data, absolute length, specific growth rate, feed efficiency, feed confersion, survival rate, water quality. The data was analyzed by using Analysis Of Variance (ANOVA) at 5% significance level. The Parameters that were significantly different were followed by the DUNCAN test at 5% significance level. Further more, The addition of E. Cottonii flour from bioflocculant fermentationto commercial feed can increase the absolute weight and absolute length of tilapia (O. niloticus), butdoes not affect the specific growth rate, efficiency of feed utilization, feed conversion ands urvival of tilapia (O. niloticus). The addition of 20% concentration of e. cottonii flour into commercial feed is the best treatment because it can increase the absolute length and weight of tilapia by 5,33 g and 5,30